Functioning Pituitary Adenoma with Xanthogranulomatous Features: Review of Literature and Case Report - Vasquez, Ciro A.; Downes, Angela; Kleinschmidt-DeMasters, Bette K.; Youssef, A Samy (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives We present a patient with a prolactin-secreting adenoma with extensive secondary, noninfectious, xanthogranulomatous changes due to remote intratumoral bleeding and provide a literature review of xanthogranulomas (XGs) of the sellar region with emphasis on prolactinomas with xanthogranulomatous features.Design Case report, with PubMed search of cases of sellar XG, focusing on neuroimaging and surgical approach.Results A 35-year-old male was found to have a large sellar/suprasellar calcified/cystic mass. Endoscopic transsphenoidal approach for extradural resection was performed and diagnosis made. Review generated 31 patients with the diagnosis of sellar XG. In a minority (6 patients), the underlying lesion for the XG was a pituitary adenoma. Headache was the most common presenting symptom and panhypopituitarism the most common endocrinological abnormality. Examples of hyperprolactinemia associated with sellar XG are also uncommon and due to stalk effect. Neuroimaging of XG on T1-weighted magnetic resonance imaging (MRIs) showed 18 cases (56.3%) were hyperintense, 1 case (3.13%) was isointense, 4 (12.5%) had mixed-signal intensity, and 2 (6.25%) were hypointense. On T2-weighted MRIs, five lesions (15.6%) were hyperintense, three (9.38%) were isointense, nine (28.1%) were heterogeneous, and nine (28.1%) were hypointense. Only one case (3.1%) had calcifications on computed tomography scan similar to ours. In 14 cases (43.7%), the lesions enhanced with contrast administration on MRI.Conclusion Prolactinomas with secondary xanthogranulomatous change represent a rare cause of XG of the sella. With no radiological or clinical signs specific for XG of the sellar region, preoperative diagnosis can be challenging, if not impossible.
Keywords: prolactinoma; xanthogranuloma; endoscopic transphenoidal; pituitary adenoma; craniopharyngioma